2011
DOI: 10.1111/j.1464-410x.2011.10460.x
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐term toxicity and quality of life up to 10 years after low‐dose rate brachytherapy for prostate cancer

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Prostate BXT is an established treatment option for low and intermediate risk localized prostate cancer. Long‐term studies have confirmed similar oncological outcomes for low risk disease compared with radical prostatectomy and external beam radiotherapy. This study reports long‐term toxicity for a large cohort of patients who had been followed‐up after LDR BXT for up to 10 years, with a minimum fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
(57 reference statements)
2
16
0
Order By: Relevance
“…At the other extreme, only 0.9 % of hospitals perform as many as 166-170 RALPs. Emara et al (2011) employed graphic techniques to describe the effect of treatment on the primary study endpoint in their study. Their research evaluated the urinary and bowel symptoms, quality of life, and sexual function of men followed for 5-10 years after treatment with low-dose rate brachytherapy for prostate cancer at their cancer center.…”
Section: Ralp Studymentioning
confidence: 99%
“…At the other extreme, only 0.9 % of hospitals perform as many as 166-170 RALPs. Emara et al (2011) employed graphic techniques to describe the effect of treatment on the primary study endpoint in their study. Their research evaluated the urinary and bowel symptoms, quality of life, and sexual function of men followed for 5-10 years after treatment with low-dose rate brachytherapy for prostate cancer at their cancer center.…”
Section: Ralp Studymentioning
confidence: 99%
“…Grade 2 and 3 or grade 4 rectal toxicity occurs in 2 to 12% and 0.4 to 2% of patients, respectively [31]. …”
Section: Ldr Brachytherapymentioning
confidence: 99%
“…In a report on long-term toxicity after LDR brachytherapy [33], patient quality of life and sexual function up to 10 years after prostate brachytherapy were analyzed. The results confirmed that brachytherapy had a favorable side effect profile over the long term with regard to potency and urinary and bowel toxicity.…”
Section: Ldr Brachytherapymentioning
confidence: 99%
“…In addition to the physiological repercussions, post-RT pelvic symptoms may restrict daily living activities (DLA), social interactions, and self-perception of health. The greatest problems are related to social and mental well-being, which may have psychological, physical, professional, social, and sexual repercussions with a significant impact on QoL [9,10].…”
Section: Introductionmentioning
confidence: 99%